Menuju Kota Tanjung Selor Dalam Perspektif Undang-Undang Republik Indonesia Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Dedi Herdianto; Otih Handayani (Jurnal Hukum Sasana, 2022)
The formation of the territory is needed so that the government is closer to its people so that it can facilitate the implementation of tasks such as the implementation of the function of serving the community, because the government is essentially formed to serve the community as stated in Article 18 of the 1945 Constitution.Tanjung Selor as the capital of North Kalimantan Province is currently still in the status of a sub-district, unlike in general the provincial capitals in Indonesia are cities. This research uses a normative research method which is carried out by focusing on the study of library materials or secondary data by using the Legislative Approach (Statute Approach) and the Conceptual Approach (Conceptual Approach). The results of this study conclude that firstly, the Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government, the formation of new regions is carried out by means of Regional Expansion and Merger as stipulated in Article 32 and the technical implementation is stated in Article 33 for ExpansionRegions and Article 44 for Regional Merger.second, the formation of Tanjung Selor City by regional expansion will be easier than through merging the regions, by merging the four sub-districts in Bulungan Regency. third, Bulungan Regency as the parent area, has six sub-districts by making Tanjung Palas District the district capital. Fourth, the merging of regions to form Tanjung Selor City as a new area, will experience many obstacles. especially to fulfill administrative requirements as well as basic requirements for regional capacity.